Perbedaan Pengetahuan tentang Makanan Pendamping ASI pada Ibu dengan Balita Gizi Kurang Usia 6-24 Bulan Sebelum dan Sesudah Mendapatkan Penyuluhan di Desa Mudung Kecamatan Kepohbaru Bojonegoro - Widyaningtyas, Prasita Ayu (citeus, 2019)
Baby growth can be hampered if only given breast milk without getting breast milk supplementary food (MPASI) after the age of 6 months, because nutrients are not fulfilled for growth and development. However, if MPASI is given early it can cause negative problems in infants such as allergies and digestive disorders. One of the causes of malnutrition is due to the lack of knowledge of mothers about giving complementary feeding to infants. So that the mother provides complementary feeding at an earlier age and the type of food that is not suitable for the baby's age. This study aims to determine the differences in knowledge about complementary foods in mothers with underweight children aged 6-24 months before and after getting counseling in Mudung Village, Kepohbaru Bojonegoro Subdistrict. This study uses the pre-experimental method with the type of research using the one group pre test post test design. The sample in this study used a total sampling of 13 people. The data collection method used is a knowledge questionnaire. Data analysis was done by paired t test. Based on the results of the statistical test with paired t test obtained p value of (0.047) where the value of p value <0.05. Based on the results of the study it can be concluded that there is a significant difference between mother's knowledge about MP ASI to children aged 6-24 months before and after getting counseling. It is expected that mothers can apply complementary feeding behavior to infants aged 6-24 months correctly and accordingly in order to improve the nutritional status of infants and follow-up health workers to further improve health counseling to further improve health counseling about complementary foods.